IMBIBITION EFFECT OF IMMERSION HYDROCOLLOID IRREVERSIBLE ALGINATE IN SODIUM HYPOCHLORITE SOLUTIO - Siti Coryniken; Didin Kustantiningtyastuti; Afriwardi Afriwardi (Andalas Dental Journal, 2015)
materials have character that absorb water it is imbibition that can affect the dimensional stability when immersed in disinfectant . The purpose of this study is to see the effect of imbibition at alginate impression material immersed in a disinfectant solution of Sodium Hypochlorite .The method used was experimental with pretest and posttest with control group design . The mold were diameter of 28 mm and height 18 mm .the impression were immersed in sodium hypochlorite 0.5 % and 1 % for 3 minutes , 5 minutes and 10 minutes . Imbibition weight calculation is done by using digital scales.The results showed that the presence of imbibition on impression material alginate that immersed in Sodium Hypochlorite solution for 3 minutes , 5 minutes and 10 minutes . Statistical Test Two Way Repeated Measure ANOVA showed a significant difference ( p< 0.05 ) in minutes imbibition , while the concentration of the solution had a significant difference ( p > 0.05 ) .The conclusion of this study is the alginate impression material has the effect of imbibition to immersion Sodium Hypochlorite solution. Keywords : hydrocolloid Alginate , Sodium Hypochlorite , imbibition effects , immersio